Does social defeat mediate the association between childhood trauma and psychosis? Evidence from the NEMESIS‐2 Study. (25th November 2013) - van, M.; van, J.; Gunther, N.; van, C.; de, R.; ten Have, M.; van, S.; Bak, M.; Myin‐Germeys, I.; van, R.
<x xml:space="preserve">Abstract</x> Objective Based on theoretical considerations and animal studies, mediation of 'social defeat' (SD) in the association between childhood trauma (CT) and psychosis was investigated. Method Trained interviewers administered a structured interview assessing CT, psychotic experiences and other psychopathology in 6646 participants in the second Netherlands Mental Health Survey and Incidence Study (NEMESIS‐2). Results Childhood trauma was associated with psychotic experiences making up the extended psychosis phenotype (EPP), as well as with a diagnosis of psychotic disorder (PD). Similarly, CT was associated with a priori selected items indexing SD (discouraged, hopeless, worthless, loss of self‐confidence, low self‐esteem, better off dead, suicidal thoughts) and with a measure of affective dysregulation (AD), which in turn were also associated with psychosis. While SD and AD individually acted as mediators in the association between CT and EPP, only SD acted as a mediator in the association between CT and PD. Cannabis use did not mediate the association between CT and EPP or PD. Conclusion The present results suggest a developmental model implicating SD as an important mediator in the link between childhood adverse experiences and later development of psychotic experiences. The combined mediation by SD and AD is compatible with an 'affective pathway' to early psychosis.